Two- to eight-month-old infants’ perception of dynamic auditory-visual spatial co-location - Bremner, J. Gavin (2011)
From birth, infants detect associations between the locations of static visual objects and sounds they emit, but there is limited evidence regarding their sensitivity to the dynamic equivalent when a sound-emitting object moves. In four experiments involving 36 2-month-olds, 48 5-month-olds and 48 8-month-olds, we investigated infants’ ability to process this form of spatial co-location. Whereas there was no evidence of spontaneous sensitivity, all age groups detected a dynamic co-location during habituation, and looked longer at test trials in which sound and sight were dislocated. Only 2-month-olds showed clear sensitivity to the dislocation relation, although 8-month-olds did so following additional habituation. These results are discussed relative to the intersensory redundancy hypothesis and work suggesting increasing specificity in processing with age.